Research on corporate reputation: a bibliometric review of 43 years (1977-2020) - Mohd Sofian, Fatimah Noor Rashidah; Abdullah, Khairul Hafezad; Mohd-Sabrun, Ibrahim (Regional Information Center for Science and Technology, 2023)
Corporate reputation is vital in today's uncertain and challenging business environment. It is crucial for firms' long-term viability, prominence in a competitive market, and relationship with the stakeholders. Research on corporate reputation has been increasing tremendously. This study aimed to perform a bibliometric analysis to find the trends in corporate reputation publications, influential countries, institutions, sources, and scholars and propose a model that could impact corporate reputation. The keyword "corporate reputation" was used as it is a collective view of all stakeholders, by using the TITLE-ABS-KEY, inserted with quotation marks. 1807 publications from 1977 to 2020 were extracted from the Scopus database. Data were exported to Microsoft Excel, Publish or Perish (PoP), and VOSviewer. The trends show increased corporate reputation research, with most corporate reputation studies focusing on business, management, and accounting. The United States accounted for nearly half of the corporate reputation publications, with New York University being the most productive institution. Some of the scholars have been mentioned in this paper. A proposed model has been developed, consisting of corporate image, e-communication, stakeholder, philanthropy, and leadership as the variables that could impact corporate reputation. This model could be further explored using qualitative or case studies. Also, contingency theory could be explored in the corporate reputation area. This study's contribution provides scholars with an overview on the corporate reputation research area.